Hepatotoxicity of monoterpenes and sesquiterpenes - Zárybnický, Tomáš; Boušová, Iva; Ambrož, Martin; Skálová, Lenka (Archives of toxicology, 2018)
Public interest in natural therapies has increased significantly over past decades. Herbs and herbal products are extensively consumed worldwide and they are generally considered as safe. However, this may not always be true as many cases of herb-induced liver injury are reported every year. The liver is a frequent target tissue of toxicity from all classes of toxicants as liver structure and function predispose it to high sensitivity to xenobiotics. The present review is focused on the hepatotoxic properties of monoterpenes and sesquiterpenes, plant secondary metabolites that represent the major components of essential oils wildly used in folk medicines, pharmaceutical industry and cosmetics. Most of these terpenes easily enter the human body by oral absorption, penetration through the skin, or inhalation leading to measurable blood concentrations. Several studies showed that some monoterpenes (e.g., pulegone, menthofuran, camphor, and limonene) and sesquiterpenes (e.g., zederone, germacrone) exhibited liver toxicity, which is mainly based on reactive metabolites formation, increased concentration of reactive oxygen species and impaired antioxidant defense. There is a high probability that many other terpenes, without sufficiently known metabolism and effects in human liver, could also exert hepatotoxicity. Especially terpenes, that are important components of essential oils with proved hepatotoxicity, should deserve more attention. Intensive research in terpenes metabolism and toxicity represent the only way to reduce the risk of liver injury induced by essential oils and other terpenes-containing products.
Keywords: seskviterpeny; Liver; rostliny; Animals; lidé; Sesquiterpenes; oleje prchavé; monoterpeny; Chemical and Drug Induced Liver Injury; Plants; játra; Humans; Oils, Volatile; reaktivní formy kyslíku; Monoterpenes; Reactive Oxygen Species; zvířata; lékové postižení jater